METODE ISTINBAṬ (PENGGALIAN) MAQASID PRESPEKTIF ABDULLAH IBN BAYYAH - Yuniar Indra Yahya; Moh. Minahul Asna; Muhammad Shodiq; Mohamad Anang Firdaus (AL-BAYAN INSTITUTE, 2025)
There are three methods of ijtihad maqāṣid. They include the bayāni method (substantive analysis), the qiyās method (analogical analysis), and the iṣṭiṣlāḥi method (beneficial analysis). Some familiar names in the study of maqāṣid include Ibn Asyur, Al-Syatibi, and Jaser Auda. Jaser is even referred to as the father of contemporary maqāṣid. One name that is less commonly studied compared to the previous two is Abdullah ibn Bayyah. Through a search on Google Scholar, his name appears as the title of research four times. These research topics include maqāṣid mua’amalāt, the renewal of Islamic law, political interpretations of maqāṣid studies, the concept of security according to Bin Bayyah, and human rights according to Bin Bayyah. These studies are sufficient to describe the practical aspect of Abdullah Bin Bayyah's use of his maqāṣid perspective. However, they have not yet described his methods and theories of exploring maqāṣid in one research title. Therefore, this research deems it necessary to comprehensively discuss the method of exploration (istinbāṭ) of maqāṣid according to Abdullah ibn Bayyah, as well as the similarities and differences with other istinbāṭ methods. It also highlights the distinctive features of Abdullah ibn Bayyah's istinbāṭ. Abdullah ibn Bayyah offers an additional paradigm in maqāṣid istinbāṭ, which is maqṣad al-tark. He terms it as bid’ah al-tark. Simply put, he explains that it refers to